اﻟﻌــــﻼﻗــــﺎت اﻹﺛﯾوﺑﯾﺔ -اﻻﻣرﯾﻛﯾﺔ ١٩٧٤-٢٠٠١ (Journal of the College of Education for Women, 2019)
Ethiopia enjoys close relations with the United States of America, as the last has given Ethiopia unrivaled attention through strengthening its relations with the political systems that came to power, as well as its attitudes towards issues that were obstacles in the way of those governments in order to prevent weakening of that State .Ethiopia's position and its strategic importance in the African Horn, leads the United States to maintain strong relationships with its successive rulers, and this is clear in its attitude towards Meles Zenawi's government. Despite the accusations made against that government, especially the issue of violating human rights and democratization, but we find that the United States has overlooked the practices of that government, because the United States has more important goals than other issues .Even if it gives these issues any importance, it is just to use them as a means to penetrate in the African Horn countries and control their harbors, lakes, and wealth, especially those which have oil, the main objective of U.S.A. Therefore the United States has been keen to build strong relations with Ethiopia in order to achieve its interests in the region. As well as establishing its bases in the region as Kagito and other bases that give its existence legitimacy.